Language center students' perceptions of online english language learning as proficiency - Erika Maroto Criollo; Diana Tipan Tipan; Paulina Arias Arroyo; Patricia Mena Vargas (Universidad de Cádiz, 2022)
English is one of the most widely used languages worldwide, which is why there is a need to introduce this language in the educational field, especially in higher education, since today it has become a basic need for professionals. This study was focused on analyzing students' perceptions of online English learning as proficiency at the Languages Center of Technical University of Cotopaxi. A qualitative approach and a case study method was used. As a data collection technique, an unstructured interview was applied to ten students from different careers and English levels. The results revealed that the majority of students choose English as a proficiency because it is one of the most in-demand languages for getting a job. Moreover, some students take learning English only as a mandatory requirement before graduation. Additionally, inside online English learning there are certain complications with respect to the development of speaking skills. Furthermore, low student participation is due to lack of interest or fear of making mistakes. Therefore, it is necessary to implement different techniques and methods to carry out the online teaching-learning process of English as a proficiency in an effective way and thus be able to achieve all the expectations that students have.